EDUCATION OF EARTHQUAKE ALERT APPLICATION AT PGRI MIDDLE SCHOOL BANTUR MALANG - Dewanti, Nisa; Diana, Meli; Riesmiyatingdyah; Apryanto, Frengki; Zunaedi, Rosly (Community Service Journal of Indonesia, 2024)
The Earthquake Alert Application Socialization Activity given to teachers at PGRI Middle School Bantur Malang is a form of community service in the form of delivering material and socializing the use of the Earthquake Alert Application as a guide on how to rescue when an earthquake occurs. Implementation of socialization activities on August 25 2023 at PGRI Middle School Bantur Malang. The target of this outreach activity is all teachers at PGRI Middle School Bantur. Before carrying out extension activities, there is an activity preparation process for approximately six weeks before carrying out the activities, starting from making applications to submitting permits to related parties. As a form of evaluation, this activity has attended by eight teachers, the participants participated in the activity very enthusiastically, and all participants were able to operate the application well.